Forum ekspertówNitric oxide and peroxynitrite balance in the cardiovascular system: a nanomedical approach - Maliński, Tadeusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
A small deviation from the physiological NO concentration may have a significant effect on the function of the cardiovascular system. A deficiency in NO production and concomitant increase in cytotoxic peroxynitrite (ONOO-) has been associated with dysfunctional endothelium. Low level of bioavailable NO and high level of ONOO- are features of several vascular diseases including hypertension, arteriosclerosis, stroke and myocardial infarction. This study used a nanotechnological and nanomedical approach (nanosensors) to measure the release of NO and ONOO- from a single dysfunctional endothelial cell (HUVECs, aortic, cardiac, and endothelial cells). A balance of K=[NO]/[ONOO-] was used as a criterion of endothelial function or dysfunction. Normal HUVECs produced high NO (480+35 nmol/L), low ONOO- (70+4 nmol/L) and a [NO]/[ONOO-] balance was at the level of K=3.5. In the presence of ox-LDL, this balance decreased to K=0.32+0.02. A significant decrease in [NO]/[ONOO-] was observed in hypertensive (SHR) rats (K=1.5+0.1) as compared to normotensive (WKY) rats (K=2.8+0.3). The K balance can be positively shifted by L-arginine or superoxide dismutase. In the failing heart of SHR, K value decreased to 0.38+0.04 from 2.2+0.2 for sham-operated rats. Treatment for 4 weeks with simvastatin (2.5 mg/kg/day) partially but significantly restored the [NO]/[ONOO-] balance in SHR with a failing heart. Therefore, simvastatin-induced shift of [NO]/[ONOO-] balance may contribute to the clinical usefulness of simvastatin in the treatment of the failing heart.